"Kodeks wyborczy" w świetle poglądów doktryny i orzecznictwa Trybunału Konstytucyjnego. Wybrane problemy - Eckhardt, Krzysztof (Polityka i Społeczeństwo, 2021)
The article discusses the jurisdiction of the Constitutional Tribunal and opinions of the doctrine on the subject of the introduction of single-member electoral districts in elections to the Senate, the possibility to vote by proxy and correspondence voting, a trial to extend the voting period over two days, and the introduction of limitations concerning the resources used during an election campaign. The adoption of these solutions emerged to meet the expectations of the doctrine, and fulfilled postulates of representatives of the electoral apparatus, in an essential way altering the electoral law, but simultaneously it aroused significant controversies. The Constitutional Tribunal was faced with a difficult task to evalu-ate them from the point of view of compatibility with the Constitution. Its adjudication was in advance doomed to criticism, because the Tribunal could only assume the point of view of a part of the doctrine’s representatives. The analysis carried out in this article enables the constitutional regulations concerning elections to be viewed in a new way.